Hidrolisis Pati Ganyong (Canna edulis) dengan Amilase Bakteri Flavobacterium sp. PTBT I untuk Produksi Bioetanol - Ningsih, Dian Riana; Zusfahair, Zusfahair; Fatoni, Amin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2013)
Bioethanol is an alternative energy of fuels produced from vegetable materials. Vegetable materials that can be used as rawmaterial for bioethanol is ganyong because it contains 22.60 g starch in 100 g ganyong. The production of bioethanol fromstarch material consisted of two steps, hydrolysis and fermentation. One of the steps to increase the value of bioethanolfrom starch of ganyong was hydrolysis process using thermostable amylase enzyme isolated from Flavoacterium sp.PTBT I bacteria was isolated from hot spring of Pancuran Tujuh Baturraden. The aim of this research was to use thermostableamylase to hydrolyze starch of ganyong and glucose produced to result bioethanol. The result of this research showed thatthe optimum condition hydrolysis starch of ganyong was using thermostable amylase acquired at substrate concentrationof 3% (b/v), and incubation time of about 75 minutes. The value of bioethanol increased with time of fermentation, from thefirst to fourth day, which was 0.8361; 2.2379; 5.7590 and 10.5787% (v/v), respectively.